Analysis of Time Waste in Healthcare Services Using Lean Healthcare and the 5 Whys Root Cause Analysis: Case Study Neurology Outpatient Clinic at Dr. Darsono Regional General Hospital, Pacitan - Mukti, Prasetyo; Rochmoeljati, R. (Golden Ratio of Mapping Idea and Literature Format, 2026)
Health services require speed, accuracy, and quality in order to be able to meet expectations and increase patient satisfaction. However, in practice, problems in the form of waste are still often found in the service flow, such as long queues, long waiting times, data recording errors, and inefficient manual activities. This condition also occurs at the Nerve Polytechnic of dr. Darsono Pacitan Hospital, which is the main referral hospital in Pacitan Regency. This study aims to identify forms of waste in services at the Nerve Polytechnic and provide suggestions for improvements to improve service efficiency. The method used is a Lean Healthcare approach with the help of Root Cause Analysis (RCA) and the 5 Why technique to trace the root cause of problems. The results of the analysis using BPM show that the lead time of the initial service is 127 minutes. After the implementation of the improvement recommendations, non-value added activities were completely eliminated, so that the lead time was reduced to 68 minutes, or equivalent to a time reduction of 46.5%. The improvement recommendations are focused on improving the efficiency of polyneural services through optimizing human resources, adjusting the work system, implementing 5S, utilizing information technology, digitizing medical records, and involving medical personnel in improving service quality.